Elucidating mechanisms of premature ovarian failure using a transgenic mouse model - Kaune Galaz, H (2015)
Premature ovarian failure (POF) is a condition that affects around 1% of women of reproductive age. It is idiopathic in 74-90% of cases and the mechanisms involved remain unclear. Several mouse models of POF have been described, however new models are necessary to understand the aetiology of POF and to hopefully identify candidate molecules that can be used as targets for intervention. A mouse model of POF (DM) occurs from oocyte-specific deletion of two glycosyltransferases encoded by C1galt1 and Mgat1, thus oocytes lack core 1-derived O-glycans and complex N-glycans. DM females have POF by 3 months of age exhibiting follicle depletion, elevated gonadotropins and decreased sex steroids. Female mice are fertile prior to ovarian failure producing a single small litter and thus, the DM model provides an outstanding opportunity to explore the onset of POF. In addition, since ablation of these glycans occurs only in the oocyte generates a progressive ovarian failure and POF, this model provides a unique opportunity to further our understanding of the role of the oocyte in the regulation of ovarian function and fertility. In this thesis, the influence of the abnormal endocrine environment was discarded as the origin of the altered follicle development in DM. In vitro and in vivo analysis of follicle development using follicle culture and the reaggregated chimeric ovary technique has highlighted intra-ovarian factors as responsible for the onset of POF in DM females. Finally, ovary transcriptomic analysis revealed an accumulation of changes in gene expression with age consistent with the DM phenotype. These results have highlighted potential therapies as well as genes and pathways as candidate molecules to try to reverse POF in the DM mouse model.